Stakeholder Pressure And Sustainability Report Quality - Pratiwi, Mellisa Indah; Sriani, Dewi (Universitas Serang Raya, 2025)
This research aims to investigate the effect of stakeholder pressure on the sustainability reports quality for Indonesian companies listed in the IDX80, with company size as a moderating variable. The study employs a quantitative approach, utilizing secondary data from annual reports and sustainability reports. The sampling technique used is purposive sampling, resulting in a sample size of 147. The research adopts a multiple linear regression and Moderated Regression Analysis using SPSS 2.5.0 software. The results indicate that environmental, consumer, and media pressures positively affect the sustainability report quality, while employee and shareholder pressures do not affect the quality of sustainability reports. Firm size strengthens the impact of consumer pressure on the sustainability report quality; however, firm size weakens the effect of employee and media pressures on the sustainability report quality. Additionally, firm size does not moderate the effect of environmental pressure and shareholder pressure on the quality of sustainability reports. This study contributes empirical evidence regarding the impact of stakeholder pressures on the sustainability report quality with also investigating the role of company size as moderating variable. Through this research, it is expected that companies in Indonesia will become more aware of the importance of issuing high-quality sustainability reports for the long-term sustainability of their operations